張仲景醫學倫理學思想述評: The Medical Ethics of Zhang Zongjing - YAN, Jinhai; PENG, Yanjie; YANG, Yue (International Journal of Chinese & Comparative Philosophy of Medicine, 2015)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 東漢時代的張仲景是中醫歷史最重要的醫家之一，被稱之為中國的希波克拉底。其名著《傷寒雜病論》成為中華醫學最重要的經典。在該書的序言中，張仲景系統闡述了其醫學倫理思想和行醫原則。認為醫師行醫的前提是實踐對自我與族群生命的熱愛；行醫的橋樑是用人類理性去發現健康與疾病的規律及控制的手段；行醫的準則是對醫術的認真與創新的態度。就其醫學倫理思想而言，張仲景醫學倫理的基本框架與中國傳統的儒家思想相吻合，反映了醫儒同道的精神。其思想對宋代以後“醫學儒化”的風尚具有一定的影響。作者認為，張仲景醫學倫理學亦對構建當代中國生命倫理學的構建具有啟發意義。 Zhang Zongjing (150-219), known as the Chinese Hippocrates, was one of the most eminent physicians in China during the Han Dynasty. In the Shanghailun, a famous treatise on cold pathogenic diseases, Zhang not only described past medicinal discoveries but provided regulations for contemporary medical practice. The Shanghailun is thus an important text for scholars of the history of traditional Chinese medicine. The treatise was privately transmitted with no public acknowledgment until the Jin Dynasty (265-420), when it was re-edited and rearranged. The treatise received more attention and became increasingly popular during the Song Dynasty, when a Confucian basis for medical practice was endorsed by the government. Zhang has since been regarded as a sage of Chinese medicine. The Shanghailun also became part of the compulsory curriculum at China’s Imperial Medical Academy. Zhang has a special status in the history of Chinese medicine due to his efforts to create an orthodox system of medical practice in line with the Confucian (Ru) tradition. In this paper, Zhang Zongjing’s major ideas on medical ethics and practice are explored. The author illustrates the critical role played by Zhang’s approach to medicine in the later Confucianization of medicine during the Song Dynasty, which in turn created the ideal of the traditional Confucian physician. The author also compares the ethical views of Zhang Zongjing with those of Sun Simiao (541-682), another key figure in the history of traditional Chinese medicine, who combined Confucian ethics with the moral teachings of Daoism and Buddhism. DOWNLOAD HISTORY | This article has been downloaded 237 times in Digital Commons before migrating into this platform.